2021
DOI: 10.2147/dmso.s345081
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Participant in Type 2 Diabetes Bone Fragility: TIMP-1 at Sites of Osteocyte Lacunar-Canalicular System

Abstract: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of bone fracture, but the bone mineral density (BMD) is typically normal or higher in such patients. Because the fracture risk is independent of reduced BMD, bone fragility in T2DM may be partially due to poor bone quality. The mechanisms triggering bone quality abnormalities in T2DM are complex, and include the accumulation of advanced glycation end-products, the increased inflammation, and low bone turnover. Matrix metalloproteinases (MMPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Other elements not addressed in our study that would support a reduction in bone strength would be the cortical porosity, which is associated with an increased risk of bone fractures in women ( Samelson et al, 2018 ). Abnormalities in osteocytic perilacunar/canalicular turnover have also been demonstrated in experimental type 2 diabetes ( Pei et al, 2021 ). Changes in the osteoid are especially important because they may affect bone quality and increase fragility and risk of fractures despite the presence of a normal bone mass densitometry which is common in type 2 diabetes ( Vestergaard, 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…Other elements not addressed in our study that would support a reduction in bone strength would be the cortical porosity, which is associated with an increased risk of bone fractures in women ( Samelson et al, 2018 ). Abnormalities in osteocytic perilacunar/canalicular turnover have also been demonstrated in experimental type 2 diabetes ( Pei et al, 2021 ). Changes in the osteoid are especially important because they may affect bone quality and increase fragility and risk of fractures despite the presence of a normal bone mass densitometry which is common in type 2 diabetes ( Vestergaard, 2007 ).…”
Section: Discussionmentioning
confidence: 98%
“…TIMP metallopeptidase inhibitor 1 ( TIMP1 ) is a naturally occurring inhibitor of matrix metalloproteinases (MMPs), a class of peptidases involved in the degradation of extracellular matrix. TIMP1 levels were significantly higher in the serum of T2DM patients, and raises the possibility that it plays a role in T2DM bone fragility [ 56 ]. Proopiomelanocortin ( POMC ) encodes a preproprotein that undergoes tissue-specific post-translational processes.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocytes have also been shown to be negatively impacted by T2DM. [ 18 , 19 , 20 , 21 , 22 ] Previous studies have demonstrated increased lacunar density and reduced osteocyte territorial matrix in a rat T2DM model, which is the mineralized matrix volume per osteocyte lacunar. [ 22 , 23 , 24 ] The osteocyte lacune size and the pericellular area have been reported to be reduced in diabetic pigs as well.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 , 19 , 20 , 21 , 22 ] Previous studies have demonstrated increased lacunar density and reduced osteocyte territorial matrix in a rat T2DM model, which is the mineralized matrix volume per osteocyte lacunar. [ 22 , 23 , 24 ] The osteocyte lacune size and the pericellular area have been reported to be reduced in diabetic pigs as well. [ 25 ] Others have reported alterations of the osteocyte network in mouse model of high‐fat induced T2DM and revealed the perilacunar mineralization heterogeneity was decreased.…”
Section: Introductionmentioning
confidence: 99%